Shape of the Doppler Sonographic Systolic Blood Flow Profile of the Pulmonary Artery of Healthy Racing Pigeons and the Influence of Anesthesia - Carolin Girard; Lajos Koy; Norbert Kummerfeld; Michael Pees; Michael Fehr; Marko Legler (Veterinary Sciences)
There is scant information available about the blood flow of the pulmonary artery in avian cardiology. In human medicine, the shape of the Doppler sonographic blood flow profile of the pulmonary artery can be used to access the pressure conditions of the right heart. With this background, this study focused on the examination of the acceleration and deceleration phase of the pulsed-wave Doppler flow profile of the pulmonary artery of healthy racing pigeons. The results showed a significant difference between the pulmonary artery and aorta. The Doppler flow profile of the aorta was characterized by a short acceleration phase; however, the pulmonary flow profile revealed an acceleration similar to that of the deceleration phase. Neither profile changed considerably under the influence of heart rate changes and anesthesia with isoflurane. A negative correlation of the pulmonary acceleration phase with the left diastolic A wave and the systolic pulmonary blood flow velocities could be found. This indicates the influence of pressure changes in the heart on the flow profiles. The results of this study allow for the use of the shape of the Doppler sonographic blood flow profile of the pulmonary artery in the assessment of cardiovascular diseases in avian medicine, especially in racing pigeons.